The Effect of Health Information Systems on the Administrative and Medical Performance in the Higher Educational Ministry Hospitals: The Case Study of Al-Mouwasah University Hospital in Damascus - كراز, جورج; الحسن, وسيم; أبو شديد, وئام (Latakia University Journal -Engineering Sciences Series, 2021)
Ñ  ABSTRACT Ñ This research aims to identify the health information systems used in the Ministry of Higher Education hospitals, by studying the experience of Al-Mouwasat University Hospital in transfer and adoption this technology, and use it in generalizing to the rest of the Syrian hospitals. It also aims to analyze the actual reality of hospital readiness and its impact on the efficiency of health information systems and on the medical and administrative fields of business and decisions. The research includes: A theoretical study of the concept of health information systems, and the concept of electronic health. A practical study of the reality of health information systems in the hospital, through which data were collected, statistically analyzed, and hypotheses tested. The research gives a number recommendations: Importance of preparing strategic plans for developing health information systems. Interesting in continuous training and qualification of employees, and the need to support the informatics department with specialized technical staff. Applying the unified electronic health record for the patient nationwide